2019
DOI: 10.1021/jacs.9b05360
|View full text |Cite
|
Sign up to set email alerts
|

Photocarboxylation of Benzylic C–H Bonds

Abstract: The carboxylation of sp 3 -hybridized C–H bonds with CO 2 is a challenging transformation. Herein, we report a visible-light-mediated carboxylation of benzylic C–H bonds with CO 2 into 2-arylpropionic acids under metal-free conditions. Photo-oxidized triisopropylsilanethiol was used as the hydrogen atom transfer catalyst to afford a benzylic radical that accepts an electron from the reduced form of 2,3,4,6-tetra(9H-carbazol-9-yl)-5-(1-phenyle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
139
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(150 citation statements)
references
References 62 publications
5
139
0
6
Order By: Relevance
“…The group of König has since reported on an elegant carboxylation of benzylic C-H bonds by merging HAT catalysis with RRPCO (Scheme 8). 13 First, a thiyl radical is generated via oxidation and subsequent deprotonation of a thiol HAT catalyst. The thiyl radical then abstracts a benzylic H atom to generate a benzylic radical and reform the thiol catalyst.…”
Section: Visible-light Photoredox Mediated Transformationsmentioning
confidence: 99%
“…The group of König has since reported on an elegant carboxylation of benzylic C-H bonds by merging HAT catalysis with RRPCO (Scheme 8). 13 First, a thiyl radical is generated via oxidation and subsequent deprotonation of a thiol HAT catalyst. The thiyl radical then abstracts a benzylic H atom to generate a benzylic radical and reform the thiol catalyst.…”
Section: Visible-light Photoredox Mediated Transformationsmentioning
confidence: 99%
“…After adding TEMPO at the initial stage of the reaction, no polymer was formed within 6 h. In the another run, TEMPO was added to the reactant after the reaction was carried out for 6 h. Then, the reaction was continued for another 6 h. The result showed that the M n of the product at 12 h was basically consistent with the M n of the product at the first 6 h (Figure S4, Supporting Information), which further proved that the reaction is free radical mediated. Taking the above results, the study of Meng et al [ 53 ] and the mechanism of thiol–ene radical reaction by Hoyle et al [ 5 ] into account, we speculated the reaction mechanism of the reaction ( Figure ). DPAB is converted to an excited state (DPAB*) under visible light, (DPAB*) and reacts with SH to generate (DPAB) − and (SH) + , and then (SH) + generates a S and H + .…”
Section: Resultsmentioning
confidence: 69%
“…We tentatively proposed a photoinduced free radical coupling reaction (Scheme ). This mechanism combines features proposed by Yang, Meng and Seo for abstraction of H atom and photoredox‐catalyzed α‐amino radical couplings respectively. During this photo‐introduced process, the triplet state of the excited BP would abstract hydrogen from the C–H bonds on a polymer surface and form carbon‐centered radicals .…”
Section: Resultsmentioning
confidence: 99%